Role of Different Adjunctive Protective Devices to Reduce Operator Radiation Exposure in Percutaneous Coronary Procedures: The RAPTOR Study - Alessandro Sciahbasi; Nicolò Salvi; Roberto Patrizi; Cristian Di Russo; Maria Cera; Alessandro Bocci; Francesco Starnazzi; Silvio Fedele; Antonino Granatelli (Journal of Interventional Cardiology)
Objective. To compare the relative effectiveness of different anti-Rx devices in terms of radiation dose absorbed by operators during percutaneous coronary procedures (diagnostic or interventional). Background. Direct comparisons among different adjunctive anti-Rx devices during percutaneous coronary procedures to reduce operator radiation exposure are lacking. Methods. We retrospectively analyzed the last 200 percutaneous procedures performed by a single operator according to the use of adjunctive protective devices (group 1) or standard anti-Rx setting (group 2). Subsequently, the procedures in group 1 have been divided according to the protective device utilized (homemade pelvic drape with under-table curtain, or RADPAD drape, or the STAR System device, or the Rampart shield). The primary endpoint was the operator radiation dose at the thorax. Results. Groups 1 and 2 did not show significant differences in terms of anthropometric data or cardiovascular risk factors. The use of adjunctive anti-Rx devices was associated with a significant reduction in operator radiation exposure compared to standard radioprotection (12.8 μSv [7–21] and 22.6 μSv [11–36], respectively; p<0.0001). Globally, the anti-Rx devices utilized were associated with a reduced operator radiation exposure (11.7 μSv [2–19] for homemade drapes, 13.5 μSv [9–29] for RADPAD drape, 15 μSv [11–30] for STAR Board System, and 8 μSv [5–19] for Rampart; p<0.0001) with the homemade drapes and the Rampart system showing a lower operator exposure. Conclusions. The use of anti-Rx devices during percutaneous coronary procedures is associated with a significant lower operator radiation exposure with the greater effect obtained with pelvic drapes and the Rampart system.